Post-pregnancy recurrent biliary colic with intraoperative diagnosis of limy bile syndrome. (June 2021) - Migliore, Marco; Giraudo, Giorgio; Gianotti, Laura; Testa, Valentina; Borghi, Felice
Abstract: Introduction: Limy bile syndrome (LBS) is an unusual condition in which gallbladder and/or bile ducts are filled with paste-like radiopaque material with a high calcium carbonate content. It can be rarely associated with PTH disorder and hypercalcemia. Presentation of case: A 35-year-old woman presented with epigastric and right hypochondrium pain since a few hours. Similar attacks occurred in the past months soon after a pregnancy with vaginal delivery. Laboratory findings were not significant. The abdominal ultrasound highlighted a micro-lithiasis of gallbladder without complications. Considering the recurrent biliary attacks, laparoscopic cholecystectomy was performed with intraoperative diagnosis of LBS. A subsequent endocrinological screening highlighted a normocalcemic hyperparathyroidism associated with Vitamin D deficiency, likely related to the recent pregnancy and not to LBS. Discussion: LBS is a rare condition with not clear etiology, frequently associated with cholelithiasis, of which it shares clinical presentation and potential complications. Diagnosis of LBS is based on abdominal X-ray/computed tomography scan, or it could be an intraoperative finding. The gold standard treatment is represented by laparoscopic cholecystectomy. The pregnancy with its related cholestatic phenotype could facilitate the LBS manifestation. An endocrinological screening should be performed to rule out a concomitant calcium metabolism disorder. Conclusion: Knowledge of this rare condition could help general surgeons handle it properly. Highlights: LBS is a rare condition characterized by a gallbladder and/or bile ducts filled with a a high calcium carbonate content LBS could be an incidental finding during cholecistectomy or preoperative diagnosed by abdominal X-ray/CT scan The gold standard of treatment for LBS is laparoscopic cholecystectomy A postoperative endocrinological screening should be performed to rule out a concomitant calcium metabolism disorder